SC-CFDMA uplink symbol synchronization method based on multi-rate satellite-ground loop - Dan DING; Nai-ping CHENG; Yu-rong LIAO (Tongxin xuebao)
SC-CFDMA(single carrier code and frequency division multiple access) system,whose synchronization is more difficult than that of common orthogonal multi-carrier systems,requires the symbol synchronization to achieve a chip-level precision.Therefore,a synchronization method based on multi-rate satellite-ground loop is proposed.This method extends the closed-loop control on the non-sampling points of the loop through raising the control rates of some loop components,so as to promote the adaptability to users with different speeds.Besides,the state-space equations of the loop and related components are derived.The Matlab simulation results show that,even in GEO satellite system,the synchronization method proposed can adjust the SC-CFDMA uplink symbol timing errors between several supersonic users within chip-level duration,thus providing stable communication.